Supercritical drying of chromatography media

Critical point drying with supercritical fluids effectively preserves the pore structure, surface area, and permeability of composite materials, addressing the instability issues in conventional drying methods and maintaining membrane performance over time.

JP7609853B2Active Publication Date: 2025-01-07MERCK MILLIPORE LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022515628
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-16
Filing Date
2020-09-14
Publication Date
2025-01-07
Estimated Expiration
2040-09-14

AI Technical Summary

Technical Problem

Existing drying methods for composite materials used in chromatography and biocompatible media fail to maintain consistent pore structure, surface area, and permeability in the dry state, leading to degradation of membrane properties over time.

Method used

A method involving critical point drying (CPD) using supercritical fluids, specifically carbon dioxide, where the composite material is contacted with a polar organic solvent to replace aqueous solution, then exposed to supercritical conditions to evaporate under zero surface tension, preserving the wet state properties.

Benefits of technology

CPD maintains the wet pore structure, surface area, and permeability of membranes, ensuring consistent performance and stability over long storage periods, unlike conventional drying methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609853000010
    Figure 0007609853000010
  • Figure 0007609853000011
    Figure 0007609853000011
  • Figure 0007609853000012
    Figure 0007609853000012
Patent Text Reader

Abstract

A method for critical point drying of a composite material is disclosed. After exposing the composite material to a supercritical fluid, the composite material dries as the supercritical fluid evaporates due to reduced pressure. The composite material is useful as a chromatographic separation medium.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims the benefit of priority to U.S. Provisional Patent Application No. 62 / 900,798, filed September 16, 2019; and U.S. Provisional Patent Application No. 62 / 900,155, filed September 13, 2019. [Background technology]

[0002] Supercritical fluid (SCF) technology has found many applications in various fields, especially in pharmaceutical applications such as particle and crystal engineering, where good control over the physicochemical properties of the particles produced and control over crystal formation are highly desirable. Other applications such as composite particle formation, extraction, coating, and preparation of liposomes have found deep interest in SCF technology.

[0003] The use of critical point drying (CPD) has also attracted interest in several fields requiring preservation of structure during drying, such as drying of biological specimens for scanning electron microscopy processes. In general, CPD, especially from CO2, has been found to preserve the high surface area of ​​porous materials such as silica aerogels compared to regular drying.

[0004] Furthermore, recent advances in this technology have explored the synthesis of porous materials by developing reaction processes in supercritical CO2 fluid for the synthesis of open-pore 3D metal-organic frameworks (MOFs) and the processing of disordered porous materials such as polymers, aerogels, and concrete.

[0005] Supercritical fluid technology is also successfully used for protein micronization, encapsulation in particles, creation of biopolymer microporous foams (using supercritical foaming), and supercritical impregnation to develop biomedical and pharmaceutical formulations or devices. To dry proteins with polymers, SCF can be used in various ways to generate biopolymers. The choice of method depends largely on the interaction of the supercritical fluid (e.g., CO2) with the active ingredient (e.g., protein), solvent, and coating material or polymer of interest, where the interaction of the polymer with the supercritical fluid (e.g., CO2) plays a key role.

[0006] Other drying methods can only preserve film properties over a limited storage time in the dry state. A method is needed to produce dry composite materials that exhibit consistent properties after CPD in the dry state and with storage. Summary of the Invention Problem to be solved by the invention

[0007] A method is disclosed for critical point drying of composite materials that can be used for a variety of applications, including the separation and purification of biomolecules. Specifically, the CPD technique was used to maintain or nearly maintain the wet pore structure, surface area, and permeability of the membrane in the dry state. After exposing the composite material to a supercritical fluid, the composite material dries as the supercritical fluid evaporates under reduced pressure. [Means for solving the problem]

[0008] In one aspect, the present disclosure relates to a method of critical point drying a composite material, the method comprising: a. providing a composite material comprising: i. a support member comprising a plurality of pores extending therethrough; and ii. a macroporous cross-linked gel, the macroporous cross-linked gel comprising a polymer formed from the reaction of one or more polymerizable monomers with one or more cross-linking agents; located within the pores of a support member; and the macropores of the macroporous cross-linked gel are smaller than the pores of the support member; b. contacting the composite material with a supercritical fluid at a temperature and pressure above the critical point of the supercritical fluid, where gas and liquid phases cannot be distinguished; and c. Reducing the pressure thereby critical point drying the composite material.

[0009] In another aspect, the present disclosure relates to a method of critical point drying a composite material, the method comprising: a. providing a composite material comprising: i. a support member comprising a plurality of pores extending therethrough; and ii. a macroporous cross-linked gel comprising a polymer formed from the reaction of one or more polymerizable monomers with one or more cross-linking agents; located within the pores of a support member; and wherein the macropores of the macroporous cross-linked gel are smaller than the pores of the support member, such that the composite material is wetted with an aqueous solution; b. replacing the aqueous solution with a polar organic solvent, wherein the composite material is wetted with the polar organic solvent; c. contacting the composite material with a supercritical fluid at a temperature and pressure above the critical point of the supercritical fluid, where gas and liquid phases are indistinguishable and the polar organic solvent is miscible with the supercritical fluid; and d. Reducing the pressure thereby critical point drying the composite material.

[0010] In another aspect, the present disclosure relates to a method of critical point drying a composite material, the method comprising: a. providing a composite material comprising: i. a support member comprising a plurality of pores extending therethrough; and ii. a macroporous cross-linked gel comprising a polymer formed from the reaction of one or more polymerizable monomers with one or more cross-linking agents; comprising a plurality of ligands which are biomolecules or bioions; and located within the pores of a support member; and wherein the macropores of the macroporous cross-linked gel are smaller than the pores of the support member, such that the composite material is wetted with an aqueous solution; b. replacing the aqueous solution with a polar organic solvent, wherein the composite material is wetted with the polar organic solvent; c. contacting the composite material with a supercritical fluid at a temperature and pressure above the critical point of the supercritical fluid, where gas and liquid phases are indistinguishable and the polar organic solvent is miscible with the supercritical fluid; and d. Reducing the pressure thereby critical point drying the composite material. [Brief description of the drawings]

[0011] [Figure 1A] 1 shows an exemplary composite material having a layer of an interleaf (eg, screen) in a spiral wound or roll assembly. [Figure 1B] An exemplary composite (eg, membrane disk) with a layer of interleaf (eg, screen) is shown in a membrane stack assembly in a CPD holder. [Diagram 2] Table 3 with substitution protocols for alcohol, buffer, and salt components is provided. [Figure 3A] The critical point drying (CPD) effect on membrane flux (circles) is shown in comparison with other drying methods (without stabilizer, diamonds; and with glycerin, triangles). [Figure 3B] The effect of critical point drying on binding capacity (circles) is shown in comparison with other drying methods (without stabilizer, diamonds; and with glycerin, triangles). [Figure 4A] 1 shows membrane properties after critical point dry storage at a membrane to ethanol ratio of 3.3. [Figure 4B] 1 shows membrane properties after critical point dry storage at a membrane to ethanol ratio of 4.3. [Figure 4C] 1 shows membrane properties after critical point dry storage at a membrane to ethanol ratio of 4.3. [Figure 4D] 1 shows membrane properties after critical point dry storage at a membrane to ethanol ratio of 5.6. [Figure 5A] FIG. 13 shows the effect of extraction protocols on epoxy membrane IgG dynamic binding capacity after CPD. [Figure 5B] FIG. 1 shows the effect of extraction protocols on epoxy membrane flux after CPD. [Figure 5C] FIG. 13 shows the effect of extraction protocols on epoxy membrane IgG dynamic binding capacity after CPD. [Figure 5D] FIG. 1 shows the effect of extraction protocols on epoxy membrane flux after CPD. [Figure 6] Table 4 with the critical point drying parameters and associated membrane ethanol extraction volumes is shown. [Figure 7] Table 5 is shown with the critical point drying parameters for membranes with various binding capacities and permeabilities. [Figure 8A] 1 shows the stability of various flux-based critical point dried epoxy films. [Figure 8B] 1 shows the stability of various critical point dried Protein A membranes based on flux. [Figure 8C] FIG. 1 shows the stability of various critical point dried epoxy membranes based on IgG dynamic binding capacity. [Figure 9A] 1 shows the change in epoxy membrane pore size distribution in substituted wet samples. [Figure 9B] Figure 2 shows the change in epoxy membrane pore size distribution in CPD samples after 25 days. [Figure 9C] Figure 2 shows the change in epoxy membrane pore size distribution in samples dried at 50 °C for 10 min from EtOH after 1 day. [Figure 9D] Figure 2 shows the change in epoxy membrane pore size distribution for samples dried at 50°C for 10 minutes after 1 day in water. [Figure 10A] The effect of CPD on membrane flux and IgG dynamic binding capacity compared to solvent exchange and other drying methods (i.e., from water and from ethanol) is shown. [Figure 10B] FIG. 1 shows the effect of CPD on epoxy membrane pore size properties compared to solvent displacement and other drying methods (from water and ethanol). [Figure 11] 4 shows the surface area measurements of CPD epoxy films and oven dried films. [Figure 12] Table 6 with the key parameters of the CPD run and the associated membrane alcohol extraction volumes is shown. [Figure 13A] FIG. 13 shows the effect of CPD on membrane IgG dynamic binding capacity compared to oven drying method. [Figure 13B] The effect of CPD on membrane flux compared to the oven drying method is shown. [Figure 14A] 1 shows the effect of buffer replacement protocols on Protein A membrane IgG dynamic binding capacity by CPD. [Figure 14B] 1 shows the effect of buffer replacement protocols on Protein A membrane flux capacity by CPD. [Figure 15] FIG. 1 shows the long-term stability of critical-point dried Protein A membranes substituted with an exemplary buffer protocol. [Figure 16A] 1 shows the effect of salt substitution protocols on the dynamic IgG binding capacity of Protein A membrane by CPD. [Figure 16B] FIG. 1 shows the effect of salt substitution protocols on Protein A membrane flux capacity by CPD. [Figure 17] FIG. 1 shows the long-term stability of critical-point dried Protein A membranes substituted with an exemplary salt protocol. [Figure 18] FIG. 1 shows a comparison of the effect of different substitution protocols on CPD Protein A membrane performance. [Figure 19A] Binding capacity data for CPD membranes from the AwB3 displacement protocol are shown. [Figure 19B] 1 shows flux data for CPD membranes from the AwB3 substitution protocol. [Figure 20A] Binding capacity data for CPD membranes from the limited alcohol displacement protocol AwB3-SV are shown. [Figure 20B]1 shows flux data for CPD membranes from the limited alcohol substitution protocol AwB3-SV. [Figure 21A] FIG. 1 shows a binding capacity time course study for CPD Protein A membranes substituted with protocols TP1-AWOB1 and TP2-AWOB1 (stored in 20% alcohol for 1 day). [Figure 21B] FIG. 1 shows flux time course studies for CPD Protein A membranes substituted with protocols TP1-AWOB1 and TP2-AWOB1 (stored in 20% alcohol for 1 day). [Figure 22A] FIG. 1 shows a binding capacity time course study for CPD Protein A membranes substituted with protocols TP1-AWOB1 and TP2-AWOB1 (storage in 20% alcohol for 7 days). [Figure 22B] FIG. 1 shows flux time course studies for CPD Protein A membranes substituted with protocols TP1-AWOB1 and TP2-AWOB1 (stored in 20% alcohol for 7 days). [Figure 23A] FIG. 1 shows a binding capacity time course study for CPD Protein A membranes substituted with protocols TP3-AWOB1 and TP4-AWOB1 (storage for 7 days in 16% alcohol in 20 mM phosphate pH 7.5). [Figure 23B] Flux time course studies for substituted CPD Protein A membranes using protocols TP3-AWOB1 and TP4-AWOB1 (storage for 7 days in 16% alcohol in 20 mM phosphate pH 7.5) are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] overview A method is disclosed for critical point drying composite materials that can be used for a variety of applications, including separation and purification of biomolecules. In some embodiments, the composite material is for biocompatible chromatography. In some embodiments, the composite material is a membrane. In some embodiments, the composite material is a porous polymer gel membrane. Specifically, the CPD technique was used to maintain or nearly maintain the wet pore structure, surface area, and permeability of the membrane in the dry state. Furthermore, the critical point drying method produces dried membranes that exhibit consistent properties by storage after CPD in the dry state. In some embodiments, CPD is used as a drying approach to dry biocompatible media, which have bioligands bound to the porous gel or porous gel composite, which can be used as a chromatographic medium for bioseparation, among other applications. Specifically, the CPD technique is used to dry conjugated protein-polymer materials while maintaining the structure and functionality of the biocompatible medium. In contrast, other drying methods can only preserve membrane properties over a limited storage time in the dry state.

[0013] definition For convenience, before further description of the present invention, certain terms used in the present specification, examples and appended claims are collected here.These definitions should be read in light of the remainder of this disclosure and should be understood by those skilled in the art.Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art.

[0014] In describing the present invention, various terms are used herein. Standard terminology is used widely in the filtration, fluid delivery, and general fluid processing arts.

[0015] As used herein, the articles "a" and "an" refer to one or to more than one (i.e., to at least one) of the grammatical object of the article. By way of example, "an element" means one element or more than one element.

[0016] The terms "comprise" and "comprising" are used in their inclusive and open sense, meaning that additional elements may be included.

[0017] The term "including" is used to mean "including but not limited to.", "Including" and "including but not limited to" are used interchangeably.

[0018] The term "polymer" is used to mean a large molecule formed by the joining of repeating units (monomers). The term polymer also includes copolymers.

[0019] The term "copolymer" is used to mean a polymer of at least two or more different monomers. A copolymer may be composed of a crosslinker and a monomer, if the crosslinker is a difunctional monomer.

[0020] The term "supercritical fluid" (SCF) is used to mean any chemical substance placed at a temperature and pressure above its critical point where the gas and liquid phases are indistinguishable. The key feature of supercritical fluids is that in the critical region the fluid exhibits a liquid-like density, but the viscosity and diffusivity are similar to a gas. Thus, supercritical fluids have good mixing and mass transfer properties, and their ability to solubilize any solute is naturally insensitive to both temperature and pressure. This variation in solubility at different temperatures and pressures provides the opportunity to use supercritical fluids in several applications where solubilization and precipitation / separation of solutes can be controlled by modifying the critical region conditions.

[0021] The term "Protein A" or "PrA" is used to mean a bacterial protein from Staphylococcus aureus, a protein A derivative, or a recombinant protein A that has the ability to bind with high affinity to mammalian antibodies of the immunoglobulin G (IgG) class. The gene for protein A has been cloned and expressed in E. coli, allowing for the production of large amounts of recombinant protein A and protein A derivatives. In some embodiments, protein A is an affinity ligand. In some embodiments, protein A is a protein, peptide, or recombinant protein that includes a ligand that binds to a monoclonal antibody (e.g., an IgG antibody) and a moiety that can form a covalent bond with a pendant reactive functional group (e.g., a thiol of Cys or an amine of Lys). In some embodiments, protein A is a protein, peptide, or recombinant protein that includes a ligand that binds to the Fc domain of an antibody and a moiety that can form a covalent bond with a pendant reactive functional group. In some embodiments, protein A is a protein, peptide, or recombinant protein that includes a ligand that binds to the Fab domain of an antibody and a moiety that can form a covalent bond with a pendant reactive functional group.

[0022] How to use Composite materials containing pendant reactive functional groups can be grafted with ligands through chemical reactions. For example, porous membranes containing active epoxy pendant groups can be grafted with bioaffinity ligands through nucleophilic conjugation reactions with suitable groups present on the bioaffinity ligands. The conjugate membranes can act as chromatographic media useful for bioaffinity separation of specific targets such as monoclonal antibodies. To have highly productive separation performance, the membrane platform must maintain a porous structure that provides sufficient flow permeability and desired target binding capacity, and these characteristics must be stable to storage.

[0023] In general, bioaffinity chromatographic media rely on immobilized ligand specificity, which allows them to selectively bind to a specific target among other analytes, which can be released in a subsequent step using a mobile phase that reduces the binding strength between the ligand and the target. This biological activity of the ligand is highly dependent on the geometrical as well as chemical structure of the active center, and therefore any change in either the chemical structure or the conformation is likely to affect the binding capacity of the chromatographic media.

[0024] One of the major challenges in creating chromatographic media is to immobilize specific ligands at the interface and maintain their biological activity, especially in the dry form. In general, drying protein molecules exposes them to various physical forces due to the removal of water, and to intramolecular interaction forces that put pressure on the three-dimensional structure of the large molecule, likely resulting in changes in the 3D structure that are irreversible.

[0025] Many techniques for protein drying have been tested, including lyophilization and the emerging SCF drying technique. Historically, lyophilization (also known as lyophilization) has been the preferred method for dehydrating proteins. However, there are stresses associated with the freezing process itself, especially in the freezing step, which can pose a risk of protein denaturation. Supercritical fluid drying is a relatively new technique that also involves different stresses on protein structure, as the high pressures associated with the SCF process can affect protein stability and the use of organic solvents can lead to denaturation or aggregation.

[0026] For immobilized ligands or biomolecules, the challenge is more complex because additional forces resulting from various interactions with the media surface (hydrophobic and ionic interactions) can amplify the drying effect and reduce ligand bioactivity. It is essential to control the drying process to maintain bioactivity, especially if the media surface is also affected by the drying process. While lyophilization is effective for drying proteins, immobilized biomolecules may require drying techniques that can dry both the immobilized molecule and the platform similarly, especially if the platform is a material that is sensitive to the drying technique.

[0027] The membrane platform is usually fabricated by in-situ polymerization of acrylate / acrylamide monomers and crosslinkers into a non-woven fibrous polymer substrate to obtain a porous reinforced gel material. For example, epoxy-containing membranes were fabricated using acrylate and acrylamide monomers and crosslinkers on a non-woven fibrous polymer substrate to obtain a porous gel material. The porosity and structure of the porous gel of the membrane were tailored by a heat treatment process to produce the desired properties, such as permeability and protein binding capacity.

[0028] In some embodiments, the porous epoxy membrane has active epoxy groups and can be grafted with bioaffinity ligands through nucleophilic conjugation reactions that utilize amino groups on biomolecules. In some embodiments, the epoxy membrane is conjugated with bioligands through a two-step process of coupling biomolecules through nucleophilic addition reactions, followed by a capping step to reduce the active epoxy groups on the surface. In some embodiments, the conjugated membrane can act as a chromatographic platform to perform bioaffinity separation of specific targets, such as monoclonal antibodies. To have good separation performance, the conjugated membrane has a good porous structure with high surface area and good permeability, as well as maintaining the immobilized ligand bioactivity.

[0029] Drying of the conjugate membrane can increase the stability of the ligand, increase the shelf life of the biopolymer, facilitate material handling, and reduce the risk of contamination. While drying the biocompatible medium, two components must be considered: the stability of the immobilized ligand and the stability of the polymer support.

[0030] However, the dry properties of the structures obtained in this way have been found to change over time. Without being bound by theory, the sensitivity of the membrane gel to the drying process may be related to the gel's pore structure, which may be irreversibly altered during the drying process. In particular, drying the membrane gel from an aqueous wet phase with a relatively high surface tension may expose the gel structure to high shear forces during the removal of water in the drying step.

[0031] For example, drying of conjugated biocompatible membranes has been found to be challenging as the membrane functionality and chromatographic performance change with the drying process and continue to deteriorate over time. This has been observed for epoxy-group-containing membranes, which showed limited stability when dried either at room temperature or at higher temperatures (40-50 °C). In addition to the membrane platform sensitivity, ligand sensitivity to the drying process stress cannot be ignored and can be responsible for the loss of bioactivity.

[0032] Without being bound by theory, it is also expected that the ligands may be affected by water removal, which exposes the protein to various intra- and intermolecular interaction forces in the vicinity of the membrane surface. Biomolecule-surface interaction forces may change the spatial structure of the protein, leading to denaturation and loss of activity.

[0033] Critical point drying offers the opportunity to dry membranes from a supercritical fluid (e.g., carbon dioxide) phase under very low surface tension conditions that minimize these forces on the membrane gel structure, thereby preserving wetting properties. That is, SCFs provide an essentially zero surface tension environment to dry materials due to their unique fluid properties at critical conditions where the gas and liquid phases may be indistinguishable.

[0034] Carbon dioxide is a good supercritical fluid candidate for critical point drying because it can reach the supercritical state under relatively mild conditions compared to other liquids or gases. For example, the critical point of water is 374 °C and 228 × 10 5 Pa (228 bar), and these conditions can result in irreversible changes to many materials of interest. That is, the critical point of water presents a more difficult to reach and extreme set of conditions that can affect polymers and ligands not only physically, but in some cases chemically. In contrast, the critical point of carbon dioxide is 31.2 °C and 73.8 × 10 5 The CO2 pressure is 100 MPa (73.8 bar), which are much less likely to irreversibly alter sample properties and require less stringent instrument design and control. Additionally, CO2 is non-toxic and cost-effective for large-scale processes.

[0035] However, due to its immiscibility with water, it cannot be transferred directly from the aqueous phase to the CO2 drying phase. Therefore, the water in the composite material (e.g., membrane) to be dried must first be replaced with a polar organic solvent (e.g., alcohol or ketone) to replace the water with the organic solvent. Thus, the replacement fluid must have good miscibility with water to enable the replacement process and must be miscible with CO2 to enable the final replacement of the membrane with the CO2 drying fluid. In some embodiments, one hurdle to overcome is the expected negative effect of exposing biomolecules to these organic solvents.

[0036] In the final step, the temperature of the chamber in which the material of interest (membrane) and the CO2 drying fluid are enclosed is raised beyond the critical point temperature and pressure into the supercritical region, followed by controlled evaporation by reduced pressure and drying in the absence of surface tension.

[0037] It is known that some proteins can be stable in some organic solvents, provided that the water content in the solvent is low (usually less than 10-20%). Minimizing conformational changes during the drying process is also known to help stabilize proteins during the drying process. Therefore, in some embodiments, to have a successful CSF drying process, the replacement protocol must include an initial step of buffer / salt replacement to provide sufficient ions (to reduce intramolecular ionic interactions during CSF drying) and rigorously use a gradient of organic solvent with low water content (<10%).

[0038] In one aspect, the present disclosure relates to a method of critical point drying a composite material, the method comprising: a. providing a composite material comprising: i. a support member comprising a plurality of pores extending therethrough; and ii. a macroporous cross-linked gel, the macroporous cross-linked gel comprising a polymer formed from the reaction of one or more polymerizable monomers with one or more cross-linking agents; located within the pores of a support member; and the macropores of the macroporous cross-linked gel are smaller than the pores of the support member; b. contacting the composite material with a supercritical fluid at a temperature and pressure above the critical point of the supercritical fluid, where gas and liquid phases cannot be distinguished; and c. Reducing the pressure thereby critical point drying the composite material.

[0039] In another aspect, the present disclosure relates to a method of critical point drying a composite material, the method comprising: a. providing a composite material comprising: i. a support member comprising a plurality of pores extending therethrough; and ii. a macroporous cross-linked gel comprising a polymer formed from the reaction of one or more polymerizable monomers with one or more cross-linking agents; located within the pores of a support member; and wherein the macropores of the macroporous cross-linked gel are smaller than the pores of the support member, such that the composite material is wetted with an aqueous solution; b. replacing the aqueous solution with a polar organic solvent, wherein the composite material is wetted with the polar organic solvent; c. contacting the composite material with a supercritical fluid at a temperature and pressure above the critical point of the supercritical fluid, where gas and liquid phases are indistinguishable and the polar organic solvent is miscible with the supercritical fluid; and d. Reducing the pressure thereby critical point drying the composite material.

[0040] In another aspect, the present disclosure relates to a method of critical point drying a composite material, the method comprising: a. providing a composite material comprising: i. a support member comprising a plurality of pores extending therethrough; and ii. a macroporous cross-linked gel comprising a polymer formed from the reaction of one or more polymerizable monomers with one or more cross-linking agents; comprising a plurality of ligands which are biomolecules or bioions; and located within the pores of a support member; and wherein the macropores of the macroporous cross-linked gel are smaller than the pores of the support member, such that the composite material is wetted with an aqueous solution; b. replacing the aqueous solution with a polar organic solvent, wherein the composite material is wetted with the polar organic solvent; c. contacting the composite material with a supercritical fluid at a temperature and pressure above the critical point of the supercritical fluid, where gas and liquid phases are indistinguishable and the polar organic solvent is miscible with the supercritical fluid; and d. Reducing the pressure thereby critical point drying the composite material.

[0041] In some embodiments, the supercritical fluid is selected from the group consisting of carbon dioxide, water, methane, ethane, propane, ethylene, propylene, methanol, ethanol, acetone, and nitrous oxide. In some embodiments, the supercritical fluid is not water. In some embodiments, the supercritical fluid is selected from the group consisting of carbon dioxide, methane, ethane, propane, ethylene, propylene, methanol, ethanol, acetone, and nitrous oxide. In some embodiments, the supercritical fluid is carbon dioxide.

[0042] In some embodiments, one or more parameters selected from the group consisting of the total amount of supercritical fluid relative to sample volume, the number of purge cycles, the temperature during contact with supercritical fluid, the rate of replacement with supercritical fluid, the temperature during the evaporation step, the heating rate that increases the temperature, and the rate of pressure reduction may be changed in the method disclosed herein.For example, parameters that can be changed to affect the drying process include: 1) the total amount of liquid CO2 relative to sample volume (or the number of purge cycles), 2) the chamber temperature during CO2 replacement, the rate of liquid CO2 replacement, 3) the temperature set for the drying step (typically higher than Tc), 4) the heating rate at which the chamber temperature increases, and 5) the rate of CO2 pressure reduction during the evaporation step.

[0043] In some embodiments, the polar organic solvent is selected from the group consisting of acetone, acetonitrile, ammonia, t-butanol, n-propanol, ethanol, methanol, and acetic acid.

[0044] In some embodiments, the support member comprises a polymeric material selected from the group consisting of polysulfone, polyethersulfone, polyphenylene oxide, polycarbonate, polyester, cellulose, and cellulose derivatives.

[0045] In some embodiments, the composite material is a membrane.

[0046] In some embodiments, the composite material is in contact with one or more interleaf layers, hi some embodiments, the one or more interleaf layers are selected from the group consisting of screen, polypropylene, polyethylene, and paper.

[0047] In some embodiments, the crosslinked gel is a neutral hydrogel, a charged hydrogel, a polyelectrolyte gel, a hydrophobic gel, a neutral gel, or a gel that includes functional groups.

[0048] In certain embodiments, composite materials used as membranes in the present invention are described in U.S. Pat. Nos. 7,316,919; 8,206,958; 8,187,880; 8,211,682; 8,652,849; 8,192,971; 8,206,982; 8,367,809; 8,383,782; 8,133,840; 9,962,691; and 10,357,766; and U.S. patent application Ser. Nos. 14 / 190,650, 16 / 055,786, and 16 / 516,500; all of which are incorporated herein by reference.

[0049] In some embodiments, the macroporous crosslinked gel comprises macropores having an average size of about 10 nm to about 3000 nm.

[0050] In some embodiments, the pores of the support member have an average pore diameter of from about 0.1 μm to about 50 μm.

[0051] In some embodiments, the crosslinked gel comprises a pendant reactive functional group. In some embodiments, the pendant reactive functional group is selected from the group consisting of aldehydes, amines, carbon-carbon double bonds, carbon-carbon triple bonds, epoxides, hydroxyls, thiols, anhydrides, azides, reactive halogens, acid chlorides, and mixtures thereof. In some embodiments, the pendant reactive functional group is an epoxide. In some embodiments, the one or more monomers comprising a pendant reactive functional group are selected from the group consisting of glycidyl methacrylate, acrylamidooxime, acrylic anhydride, azelaic anhydride, maleic anhydride, hydrazide, acryloyl chloride, 2-bromoethyl methacrylate, and vinyl methyl ketone.

[0052] In some embodiments, the crosslinked gel comprises a plurality of ligands. In some embodiments, the crosslinked gel comprises a plurality of ligands comprising a functional group. In some embodiments, the functional group is selected from the group consisting of cationic, anionic, hydrophobic, hydrophilic, thiophilic, hydrogen bond donating, hydrogen bond accepting, pi-pi bond donating, pi-pi bond accepting, metal chelating, biomolecule, and bioion.

[0053] In some embodiments, the plurality of ligands are biomolecules or bioions selected from the group consisting of albumin, lysozyme, viruses, cells, gamma-globulins of human and animal origin, immunoglobulins of both human and animal origin, recombinant or naturally occurring proteins including polypeptides of synthetic or natural origin, interleukin-2 and its receptor, enzymes, monoclonal antibodies, antigens, lectins, bacterial immunoglobulin binding proteins, trypsin and its inhibitors, cytochrome C, myoglobulins, recombinant human interleukins, recombinant fusion proteins, protein A, protein G, protein L, peptide H, nucleic acid derived products, DNA of either synthetic or natural origin, and RNA of either synthetic or natural origin. In some embodiments, the plurality of ligands are biomolecules or bioions selected from the group consisting of gamma-globulins of human and animal origin, immunoglobulins of both human and animal origin, recombinant or naturally occurring proteins including polypeptides of synthetic or natural origin, monoclonal antibodies, bacterial immunoglobulin binding proteins, recombinant fusion proteins, protein A, protein G, and protein L. In some embodiments, the plurality of ligands is a biomolecule or bioion selected from the group consisting of a polypeptide, a protein, a recombinant protein, a bacterial immunoglobulin binding protein, a recombinant fusion protein, Protein A, Protein G, Protein L, and Peptide H. In some embodiments, the plurality of ligands is Protein A.

[0054] In some embodiments, the composite material (e.g., membrane) comprises a polymer containing various ligands useful for affinity chromatography, such as chromatographic separation of biomolecules (e.g., proteins). For example, this approach can be used to introduce ion-substitution functional groups (e.g., carboxylate, sulfonate, quaternary ammonium, amine), hydrophobic interaction moieties (e.g., octyl groups by using 1-octanethiol or 1-octene), and biomolecules for bioaffinity chromatography (e.g., cysteine-protein A for monoclonal antibody purification) into the composite material (e.g., membrane).

[0055] In some embodiments, the composite material exhibits instability during and after conventional drying processes. In some embodiments, critical point drying allows for the removal of water without damaging the composite material. In some embodiments, critical point drying allows for the removal of water without damaging the ligand-containing membrane. In some embodiments, the present invention relates to methods of critical point drying a composite material such that the composite material exhibits properties comparable to an initially water-wet composite material.

[0056] In some embodiments, the method of critical point drying of the composite material improves storage of the composite material, assembly of the membrane into final devices, and stable transportation with reduced bioburden load. EXAMPLES

[0057] The following examples are provided by way of illustration. However, it will be understood that the specific details given in each example have been selected for illustrative purposes and should not be construed as limiting the scope of the present disclosure. Generally, the experiments were carried out under similar conditions unless otherwise stated.

[0058] Example 1 - General Materials and Methods chemistry Liquefied carbon dioxide (medical grade 99.99%) was obtained from PraxAir Canada Inc., absolute alcohol reagent (<0.005% water) and calcium chloride were obtained from MilliporeSigma, and buffer 10× PBS concentrate (GrowCells) was purchased from VWR.

[0059] protein Affinity-purified human IgG was obtained from Innovative Research Inc. (Novi, MI, USA).

[0060] Membrane Material Epoxy membranes were fabricated by polymerizing acrylate and / or acrylamide monomers and crosslinkers within the supporting mesh material in a UV-initiated reaction. Various functional membranes containing protein-binding groups (e.g., ionic substitution, hydrophobic interactions, and hydrophilic interactions) can be produced in a single polymerization step by introducing the appropriate functional polymerization groups into the gel polymerization solution. Wet-washed membranes may also be subjected to an additional heat treatment step to tune their performance, final pore structure, and permeability.

[0061] The epoxy membrane was then conjugated with Protein A ligand via a nucleophilic addition reaction, in which most of the nucleophilic groups (amino or thiol groups) on the ligand molecule opened the oxirane ring, covalently binding the bioligand to the membrane gel.

[0062] Other ligands can also be conjugated to target other biomolecules or entities, such as viruses.

[0063] In a typical conjugation protocol, a membrane disk (25 mm) was mounted in a Natrix stainless steel holder and then connected to an AKTA chromatography instrument, the membrane was equilibrated with PBS, and then a solution of the ligand (Protein A) in phosphate buffer was passed through the membrane at a selected flow rate for an appropriate time period. This was followed by a buffer wash step, then passivating the unreacted epoxy groups of the membrane by passing a quenching solution through the membrane, followed by a buffer wash step to remove residual quenching solution.

[0064] Membrane performance test The permeability of the membranes (both pre- and post-conjugation states when ligands were conjugated to the membranes containing pendant reactive groups) and their binding ability to specific biomolecular targets were assessed.

[0065] For permeability, flux tests are performed at a specified pressure (100 kPa), typically using water as the test fluid, to measure the amount of fluid passing through a specific membrane surface area, and the final permeability results are reported in kg / m 2 It is expressed in h.

[0066] Membrane binding capacity was measured by determining the amount of selected protein captured by a test volume membrane under defined flow conditions (i.e., dynamic binding capacity, dBC) and expressed as mg protein bound / mL of membrane.

[0067] For membrane bioaffinity, binding capacity was measured by determining the amount of IgG protein captured by the active membrane volume at 10% breakthrough absorbance of a passing test solution of the target molecule (IgG in this case) in buffer. The dynamic binding capacity (dBC) is expressed as mg of target molecule / mL of membrane volume.

[0068] Film Format Format A Membrane samples were typically solvent exchanged and critical point dried in roll format. The membrane strips were laminated with strips of polypropylene screen of similar width and slightly longer length (2-3 cm longer) and then rolled up (Figure 1A). The rolls were made with dimensions to fit into the critical point drying (CPD) chamber sample holder (most often 4 cm wide and ~4.5 cm OD) or, in some cases, directly into the instrument chamber itself (<5.5 cm wide and <5.8 cm OD).

[0069] Format A' Membrane samples were displaced and dried in a handmade roll format. Protein A membrane strips (~4 × 36 cm) were laminated with a PP screen of similar width and slightly longer strips (2-3 cm longer) and then rolled up (Figure 1A). The screen was used to improve the displacement process and the consistency of the process. The rolls were made with dimensions to fit into the instrument holder (most often 4 cm wide and ~4.5 cm OD) or in some cases directly into the instrument chamber itself (<5.5 cm wide and <5.8 cm OD). A wire was used to hold the interleaved rolls together during the displacement process, which was performed in a 200 mL beaker, and then removed just before placing the roll into the holder (or chamber for larger roll setups).

[0070] Format B Membrane samples were critical point dried as a displacement stack of membrane and screen disks of the same diameter. After complete displacement in separate containers with appropriate solution volumes at each step according to the protocol, the membrane disks (25 mm) were stacked in a modified sample block (with an ID of 25 mm) displaceably equipped with screen disks of the same diameter, as shown in Figure 1B. The screen disks act as separators to facilitate better mixing and accessibility during the solvent displacement step, as well as the CPD drying process, where the displacement of alcohol with CO2 is critical for successful drying. The stack was briefly immersed in a fresh amount of absolute alcohol and then mounted on the displacement chamber of the CPD instrument.

[0071] Water / Ethanol Substitution Protocol The critical pressure and temperature of carbon dioxide are 73.8×10 5 The pressure is 100 Pa (73.8 bar) and 31.2 °C. These mild conditions to reach a supercritical fluid state make carbon dioxide a suitable choice to perform critical point drying while maintaining the fragile structure during the process. However, the low miscibility of water in CO2 necessitates replacing the water with ethanol, a more CO2-miscible intermediate liquid phase that can be easily replaced with liquid carbon dioxide prior to the drying process.

[0072] The membrane roll was typically transferred to an ethanol replacement fluid through a water-ethanol gradient to finally replace the aqueous phase in the membrane with absolute alcohol with a very low water content. Several protocols with different numbers of steps, variable alcohol content, and residence times were investigated. Mainly two protocols were investigated: Protocol A with five short steps with a gradual decrease in water content (Table 1) and Protocol B with eight steps (Table 2). [Table 1]

[0073] [Table 2]

[0074] Even though CO2 is the most suitable choice for the CPD process, its poor miscibility with water requires the replacement of the aqueous phase (in this case the buffer solution) with alcohol, a more miscible liquid phase that can easily replace the liquid carbon dioxide. Typically, the replacement protocol for CPD involves replacing the subject in an ascending gradient solution of alcohol in water, ending with an absolute alcohol soak / replacement to remove all water before proceeding to the SCF step, and finally evaporating the CO2 by reducing the pressure to perform the supercritical to gas phase transition.

[0075] However, since the conjugate form has the ligand bound to the membrane, the displacement protocol was modified to minimize or mitigate the expected negative effects of exposure of the ligand molecules to organic solutions. First, the first step of the displacement protocol is designed to promote the concentration of the membrane and the ligand with counterions by performing a prolonged soak in a buffer solution. Second, instead of gradually transferring the membrane to an absolute alcohol phase, the membrane was transferred directly from a 100% aqueous phase to a 90% alcohol-containing phase to avoid exposing the protein to an alcohol mixture with a high water content that may promote denaturation. Finally, the displacement holding time was limited to avoid prolonged exposure to the alcohol solution.

[0076] Several protocols were investigated using different steps and varying alcohol solutions, which are detailed in the Examples section. To demonstrate the importance of the modified substitution protocol, the typical protocol used for CPD of epoxy membranes (Protocol C - Table 3; Figure 2) was also tested with Protein A conjugated membranes, as detailed in the Examples below.

[0077] As described previously, the 25 mm disks were substituted in separate containers with the appropriate solutions / volumes according to the specific substitution protocol. Once the substitution process was finished, the membrane coupons were stacked with a screen separator and the entire holder was placed in a 200 mL beaker with fresh absolute alcohol solution and finally transferred to the instrument chamber.

[0078] critical point drying Siphon tube for discharging liquid CO2 (~55×10 5The critical point drying (CPD) process was carried out using a Leica EM CPD300 equipped with a liquid carbon dioxide tank with a pressure of 1000 Pa (55 bar), and a separator bottle to collect the extracted ethanol from the outlet CO2 / alcohol mixture. In a typical automatic mode operation, the membrane roll was placed in a cylindrical holder in the chamber, anhydrous ethanol solution was added until the sample was mostly covered with ethanol, and then the lid was tightened to seal the chamber. Alternatively, the chamber may be first cooled to a set temperature and then the membrane roll loaded as previously described.

[0079] The instrument program automatically initiated the process by cooling the chamber to a specified fill temperature (10 or 15°C) and then supplying liquid CO2 to fill the chamber. After a pre-defined delay period set to allow for initial mixing of the alcohol and carbon dioxide liquid, the alcohol purge process begins by injecting liquid CO2 over multiple cycles (12-99 cycles), where fresh CO2 replaces a portion of the solution mixture in the chamber in a continuous manner in each cycle while maintaining the pressure in the chamber within a certain range (maintaining the CO2 in a liquid state). In addition to setting the number of replacement cycles, it is also possible to set the rate at which CO2 is supplied through the chamber.

[0080] Once the purging process is complete, the instrument is switched to a heating step, in which the chamber temperature is raised above the critical temperature (34-36 °C) and the pressure is increased to the critical pressure (>74 × 10 5 The membrane was immersed in the supercritical CO2 liquid at a pressure set higher than 1×10 Pa (74 bar). In the final step, the evaporation process was carried out by slowly releasing the CO2 and lowering the pressure while maintaining the temperature, which allowed the transition from the supercritical phase to the gas phase in the absence of any significant surface tension. The final pressure at which the dry membrane was removed from the chamber was set at 1×10 5 The process was terminated by bringing the pressure to 1 bar. The instrument allows some control over the heating / evaporation process as the speed can be set to three different levels.

[0081] To affect the drying process, several parameters can be varied, including: 1) the total amount of liquid CO2 relative to the sample volume (or number of purge cycles), 2) the chamber temperature during CO2 replacement, the liquid CO2 replacement rate, 3) the temperature set for the drying step (typically higher than Tc), 4) the heating rate at which the chamber temperature increases, and 5) the rate of CO2 pressure reduction during the evaporation step. Only selected protocols were investigated to demonstrate the concept of using the CPD process to obtain storage-stable dry films without implying any restrictions or limitations on any of the CPD process parameters, but simply to demonstrate the concept of using the CPD process to obtain storage-stable dry films.

[0082] Pore ​​size measurement Membrane pore size (diameter) was measured using a 3G Porometer, a capillary flow porometer (Quantochrome Instruments, Boynton Beach, FL) operated by 3GWin software (V2.2). Small disks (1.8 cm diameter) of dry membrane were immersed in Porofil wetting solution (Quantochrome Corp., surface tension = 16 dynes / cm) for 10 minutes and then gently squeezed between two pre-wetted filter paper disks (Whatman 5-70 mm) to remove excess solution, and the thickness of the wetted membrane was determined using a micrometer. The membrane disk was placed membrane-side up on a stainless steel mesh support disk in a designated holder. A metal cover was then gently placed on the holder to close it, and the test was then performed within a pressure range of 0-200 psi.

[0083] Example 2 - Comparison of critical point drying of epoxy-containing films with other drying methods and their effects on performance during storage Various batches of epoxy membranes with similar permeability, and their bioligand-derivatized forms with comparable protein binding capacities, were dried using a two-step critical point drying process. In the first step, the membranes in roll form were subjected to a water / ethanol displacement process, in which the membrane roll was placed in a displacement solvent of a specific alcohol content for a predetermined time, as outlined in displacement protocol B (Table 2), and then the reagents were decanted and a fresh predetermined amount of alcohol solution was added for the next step. In the second step, the ethanol-wet membrane roll was placed in a critical point drying instrument chamber (Leica CPD300) and subjected to a purging process to displace the ethanol with liquid CO2, followed by changing the drying chamber conditions to supercritical conditions (34 °C and 79 × 10 CO2). 5 The pressure was then transferred to a pressure of 79 bar (Pa) and finally the pressure was released to allow the supercritical fluid CO2 to evaporate.

[0084] To illustrate the impact of the CPD process on stability compared to other methods, epoxy-containing membranes were dried in an oven (50 °C-15 min) and, in a separate experiment, immersed in a 50% glycerin solution for 30 min and then dried in an oven (50 °C-15 min). The results (Figure 3A and Figure 3B) show the effectiveness of the CPD method in preserving wet membrane performance compared to the oven-drying method (with or without glycerin stabilizer). There was an initial small decrease in the binding capacity (5-10%) of the critical-point dried membranes compared to the wet membranes (Figure 3B). However, the membrane properties were essentially unchanged during the following storage-test periods.

[0085] As shown in Figures 4A-4D, long-term storage testing demonstrated that the critical point dried membrane (epoxy form) permeability (flux) did not change significantly over the 90 day test period tested. Furthermore, it was demonstrated that critical point dried membranes produce derivatized Protein A membranes with similar performance (flux and binding capacity) over the same 90 day storage period. This differs significantly from the behavior of oven-dried membranes over shorter storage times.

[0086] Example 3 - Critical point drying of epoxy-containing films using different displacement protocols For a drying process using supercritical fluids to be successful, the water must be removed and replaced with ethanol. There are several factors that are expected to affect the water removal process: the water content in the ethanol replacement solution, the replacement time, the number of replacement steps, the interleaf screen material, and finally the membrane to solution ratio.

[0087] Two different replacement protocols with gradient ethanol content were investigated. In protocol A, the membrane is replaced with an ethanol solution to replace the water in the membrane with alcohol through a five-step replacement protocol using solutions with gradually decreasing water content to finally reach a replacement step with absolute ethanol reagent. In protocol B, the replacement process is carried out completely over eight replacement steps to replace the water in the membrane with ethanol. The two protocols A and B are outlined in Tables 1 and 2, respectively.

[0088] The results, as shown in Figures 5A-5D, reveal that when the water in the membrane was extracted (at a fixed membrane to ethanol solution ratio (1:9.5), listed in Figure 6 and Table 4), both protocols were efficient in removing water and resulted in dried membranes with consistent properties over the 90-day storage test.

[0089] Example 4 - Critical point drying of epoxy-containing films substituted with different film to alcohol solution ratios Ideally, it would be preferable to minimize the amount of alcohol required for efficient aqueous extraction, thus mitigating associated costs, handling, and waste issues, especially for large-scale operations. To demonstrate the flexibility of the CPD method for drying epoxy-containing membranes while maintaining their wet-state properties, several membranes in roll format were extracted following Protocol B while using different membrane-to-solution ratios (Figure 6, Table 4: CPD190404, CPD190409-1, and CPD190411-1).

[0090] The results (Figures 4A-4D) show that it is possible to successfully prepare membranes for critical point drying at membrane-to-solution ratios substituted with gradient alcohol solutions and that can range as low as 5.6 to 3.3. Indeed, a ratio of 9.5 also falls within the valid range, as results from early experiments (protocols A and B, Figures 5A-5D) showed that critical point drying did indeed produce storage-stable epoxy membranes at that ratio, which continued to have the same performance characteristics over extended periods after drying.

[0091] Example 5 - Critical Point Drying of Multiple Epoxy-Containing Films of Varying Permeabilities Tailoring membrane structure, porosity, and permeability for any particular application, especially for bioseparations, is a critical part of developing a successful chromatography platform, and it is important to demonstrate the ability of the critical point drying technique to preserve the wet-state performance of a variety of membranes with different properties. In this example, several epoxy-containing membranes of different permeabilities and different binding capacities (when conjugated) were substituted (Protocol B, Table 2) and critical point dried using the process parameters listed in Table 5 (Figure 7).

[0092] Again, the results (Figures 8A-8C) showed that the CPD process preserved membrane properties over extended storage times (binding capacity was measured after a subsequent ProA conjugation step). Despite differences in their performance characteristics, all critical point dried membranes maintained their initial permeability and binding capacity levels during storage (post-conjugation).

[0093] Example 6 - Effect of critical point drying on membrane porosity compared to other drying methods To demonstrate the effect of the CPD method on membrane pore size and distribution in comparison to oven drying, membrane samples were dried according to various methods and porometry tests were performed to follow the changes in pore size.

[0094] Protocol B (Table 2) was used to exchange the epoxy membrane samples with ethanol and then the membranes were dried using the following methods: A) critical point drying; B) the membranes were immersed in water and then dried in an oven at 50 °C for 10 min; and finally C) the membranes were dried directly from the ethanol in an oven at 50 °C for 10 min.

[0095] For the ethanol wet displacement samples, which served as non-dried references, the membrane coupons were substituted in 5-10 mL of Porofil solution in a beaker for approximately 10-15 minutes to displace the ethanol with Porofil test fluid prior to testing. For all other dried samples (A, B, and C), a small disk (18 mm diameter) of each membrane was immersed in Porofil solution for at least 10 minutes prior to testing (as outlined in the methods section).

[0096] The results show that the ethanol-wet control membranes have a relatively narrow pore size distribution compared to all of the dried samples. However, the changes in pore size and pore size distribution, whether water- or ethanol-derived, were not significantly greater in the CPD membrane samples compared to the oven-dried samples (Figures 9A-9D). The differences exhibited in membrane pore size characteristics generally correlate with membrane performance characteristics, i.e., smaller pore size correlates with lower membrane flux and higher binding capacity of the Protein A conjugate form (Figures 10A and 10B).

[0097] Example 7 - Surface Area of ​​Critical Point Dried Epoxy Films Compared to Oven Dried The surface area of ​​any membrane plays an important role in determining its degree of interaction with target molecules in the mobile phase, especially since most adsorption processes in bioseparations occur at interfaces. A larger accessible surface area generally means a larger binding capacity, and the opportunities for biomolecules to interact with the functional surface, whether through ionic, hydrophobic, or bioaffinity interactions, increase proportionately with the increase in surface area.

[0098] In this example, several samples of epoxy-containing films dried using the critical point drying method were analyzed for total surface area using the BET test. Additionally, oven-dried samples were also examined to compare the surface area of ​​both types of films and the effect of the drying process.

[0099] The surface area of ​​some of the CPD membranes (Figure 11) is substantially larger than that of the oven-dried samples, with only 4.3 m for the oven-dried membrane. 2 / g, the surface area of ​​the CPD membrane is 22-25 m 2 / g. This demonstrates that the CPD process results in a significantly higher total surface area than oven drying, which very likely results in a significantly higher protein binding capacity (a surface-limited process). Presumably, gel collapse by simple oven drying significantly reduces the total membrane surface area and associated binding capacity.

[0100] Critical point drying (from liquid CO2) has been proven to be a suitable process for drying membranes to maintain their wet state properties and maintain membrane properties over long storage times. The permeability and binding capacity of the conjugate forms of such membranes change dramatically when dried from water or ethanol, even at relatively mild temperatures, but their counterparts dried using critical point drying had similar permeability and binding capacity to their wet forms. It has been shown through various examples that the critical point drying technique can reduce the drying effect on membrane gel pore size and produce membranes with high surface area compared to other methods.

[0101] Example 8 - Critical Point Drying of Protein A Membranes Compared to Conventional Drying In this example, a typical CPD method was used to dry a Protein A conjugate membrane and the resulting material was compared to another drying method for a Protein A membrane (oven drying at 40° C. for 20 min).

[0102] Protein A membranes were made by conjugating Protein A ligand to an epoxy-containing membrane (disc format) following the conjugation method outlined in the Membrane Materials section of Example 1. The membrane coupons were tested prior to drying to determine their binding capacity and their flux to establish a wet baseline.

[0103] In the second stage, the membrane discs were displaced using Protocol C, a typical gradient displacement system using an alcohol solution, as outlined in Table 3 (Figure 2). In the third stage, to promote better mixing and displacement efficiency, the membrane discs were loaded into a holder with a screen disc of the same diameter as the separator, and then the holder with the membrane disc / screen stack was loaded into the CPD instrument, and the CPD process proceeded as described in the experimental section (Figure 12; Table 6).

[0104] To demonstrate the contrast between the CPD approach and typical drying methods on Protein A membranes, and the effect of both processes on membrane stability, an additional sample of Protein A membrane was dried in an oven for 20 min at 40° C. Both materials (critical point dried and oven dried) were examined and their binding capacities (dBC) and permeability (flux) were identified and compared.

[0105] The results (Figures 13A and 13B) clearly show how the CPD method preserved the membrane permeability with only minor changes in membrane flux, whereas the oven-dried sample flux showed a significant increase after 1 day of drying. On the other hand, the results also showed a loss of binding capacity of the biocompatible membrane, suggesting that the typical substitution protocol using only an alcohol gradient did not affect the membrane platform structure, but negatively affected the ligands and caused bioactivity loss, since the dBC of the membrane was significantly decreased.

[0106] Example 9 - Critical Point Drying of Protein A Membranes Using a Buffer / Alcohol Replacement Protocol In this example, biocompatible membranes were dried using a modified substitution protocol that includes a long soaking step with buffers, with the goal of providing counterions to the protein to increase its stability when exposed to the organic phase (both alcoholic solution and liquid CO2) and high pressure during the CPD process. Two protocols were developed, namely Awb3 and Awb7, and the first step of both protocols is a relatively long soaking of the membrane in high salt buffer solutions (PBS at 5x and 10x, respectively), as outlined in Table 3 (Figure 2).

[0107] In addition to the buffer soaking step, the developed protocol avoids exposing the ligand to organic solutions with relatively large amounts of water, since intermediate mixtures of water / organic solution may increase the risk of ligand denaturation and the resulting loss of biological activity. Thus, after the buffer step in both protocols, the organic fluid content was rapidly increased from 0% to 90% in the next two steps. In general, proteins may be more stable in organic solutions with low water content. CPD proceeds as previously described (Figure 12; Table 6).

[0108] The results (Figures 14A and 14B) demonstrated that both substitution protocols were able to produce CPD membranes with properties, especially binding capacity, comparable to wet membranes. This is in clear contrast to protocol C, where the dBC of dry membranes was significantly reduced.

[0109] Additionally, the stability of CPD Protein A membranes substituted with Protocol AwB7 was investigated by testing the performance of the membranes after dry storage for selected periods of time. As shown in Figure 15, the dry membranes had generally stable performance over the test period.

[0110] Example 9A - Critical Point Drying of Protein A Membranes Using Buffer / Alcohol Substitution Protocol (AwB3) Interleaf membrane rolls were prepared as outlined in the previous section and then displaced from aqueous to essentially pure ethanol solutions using the developed protocol AwB3 (Table 7), which includes a buffer exchange step at the beginning of the substitution process. The membrane roll was simply placed into the specified amount of solution in a 200 mL beaker and then displaced for the specified time with stirring every 2-3 min. At the end of each step, the solution was gently poured off and a fresh amount of solution was added according to the composition outlined in the table. At the end of the substitution process, the membrane roll was transferred to the pre-cooled chamber of the CPD instrument and the process was run according to the specified program in automatic mode with pre-defined key parameters as shown in (Table 8). TIFF0007609853000003.tif70163

[0111] TIFF0007609853000004.tif52170

[0112] The results, as shown in Figures 19A and 19B, demonstrate the success of the drying process in preserving the membrane binding capacity and permeability. They also clearly demonstrate the stability of the dried membranes over 90 days of storage, as the binding capacity and membrane permeability are within the normal variation of the membrane and are close to the initial membrane state.

[0113] Example 9B - Critical point drying of Protein A membranes using a modified buffer / alcohol substitution protocol (AwB3-SV) In this example, a modified (shorter version) protocol was used to displace the membrane interleaf roll as outlined in Table 9 (AwB3-SV), in which the membrane was first displaced with buffer (5x PBS) and then underwent a two-step limited alcohol displacement process instead of the usual four steps in the original AwB3 protocol. TIFF0007609853000005.tif61170

[0114] The results showed that despite using the limited displacement protocol, it was still possible to produce CP dry membranes that were stable during dry storage, as shown in Figures 20A and 20B. The membranes underwent slight changes in binding capacity and flux within the first two weeks, before stabilizing over the remainder of the study period.

[0115] Example 9C - Critical Point Drying of Protein A Membranes After Storage in Biostatic Solution (20% Alcohol in Water) To illustrate the flexibility of this drying approach, the protocol included a first storage period in biostatic solution before proceeding with the alcohol replacement and CP drying process. In this case, the protocol was split into two sub-protocols: 1) preparing the membrane and transferring it to a biostatic storage solution, and 2) applying a simplified, shorter protocol, substituting the storage solution for essentially pure alcohol in preparation for the CP drying process. One protocol shows the process steps of directly transferring the membrane, replacing it in a 20% alcohol solution, then removing and storing it in a sealed PP bag for 1 (or 7) days, as outlined in (TP1-AWOB1, Table 10). In an alternative protocol (TP2-AWOB1, Table 11), the membrane roll is first replaced with a buffer solution (5x PBS) to allow for sufficient incorporation of ionic groups, after which the membrane is replaced in 20% alcohol (in water) and then stored for a short period of time (1 day for the first set, 7 days for the second set). At the end of each experimental storage period, the membranes are subjected to a replacement protocol to replace the primarily aqueous storage solution with alcohol in preparation for the CP drying process. TIFF0007609853000006.tif109170

[0116] TIFF0007609853000007.tif105170

[0117] The results of the first set (Figures 21A and 21B), in which membranes were stored for 1 day using the two alcohol replacement protocols, show that the CP drying process produced membranes that were very similar to the original wet morphology and that were essentially stable upon dry storage over the test period.

[0118] Although the presence of a buffer replacement step tends to produce membranes with a slight increase in permeability, it is worth noting that the absence of a buffer replacement step in the first protocol did not adversely affect the outcome of the drying process. This may be due to the short storage time used here (1 day) and the fact that the alcohol percentage in the replacement solution was either very low (<20%) or very high (90 and 100%). These concentrations were deliberately chosen to avoid ligand conformational changes, since proteins tend to be more stable in either predominantly aqueous solutions or pure organic solvents.

[0119] On the other hand, the results of the second set (Figures 22A and 22B), in which membranes were stored in 20% alcohol solution for 7 days, show how including a buffer exchange step prior to 20% alcohol storage (protocol TP2-AWOB1) resulted in an increase in dry membrane binding capacity, but no clear effect on membrane permeability (as measured by flux).

[0120] Example 9D - Critical Point Drying of Protein A Membranes Using a Displacement Protocol with Storage in 16% Alcohol in 20 mM Phosphate Buffer (pH 7.5) In this example, an alternative biostatic storage solution (16% alcohol in 20 mM phosphate buffer, pH 7.5) was used to store the membranes for 7 days prior to alcohol exchange and CP drying as shown in Table 12, which outlines protocol TP3-AWOB1, and Table 13, which outlines an alternative protocol TP4-AWOB1 that includes a buffer exchange step (5x PBS). TIFF0007609853000008.tif111170

[0121] TIFF0007609853000009.tif100170

[0122] The results again demonstrated the ability of the CPD process to produce dry films that resembled the wet morphology, as shown in Figures 23 A and 23 B. For both replacement protocols, the impact of the drying process was very small, although the presence of the buffer replacement step in the second protocol had slightly better results on binding capacity.

[0123] Example 10 - Critical point drying of Protein A membranes using a salt / alcohol replacement protocol In this example, the use of salts instead of buffers as a source of ions, especially multivalent cations such as divalent calcium cations, was demonstrated to modify the solvent displacement system prior to the CPD process. Divalent calcium cations are well known to affect protein structure through coordinate bonds that act to stabilize biomolecular structures in solution. Furthermore, calcium salts have good solubility in absolute alcohol solutions, an advantage that PBS buffer does not have. This allows calcium cations to be continuously supplied to the membrane during the last few steps of the displacement protocol to ensure that the cations remain in contact with the membrane before moving on to the CPD process.

[0124] Similar to the previous examples, Protein A membrane disks were made by functionalizing an epoxy-containing membrane and then following the AwB9 protocol (Table 3; FIG. 2) similarly but substituting calcium chloride solution (2 M) in water instead of the PBS buffer solution, and then critical point dried as outlined above using the key parameters listed in Table 6 (FIG. 12; Program 8).

[0125] The results (Figures 16A and 16B) showed a positive effect of incorporating calcium cations in the substitution protocol (AwB9) compared to protocol C, especially on the binding capacity which remained essentially unchanged, and only a slight initial drop in membrane flux. Long-term dry storage studies showed that membrane flux and binding capacity remained unchanged over the selected test period (Figure 17).

[0126] Comparing the results using salt-incorporated and buffer-incorporated displacement protocols with those using the additive-free flat gradient protocol (Figure 18), it was clear that the addition of salt and / or buffer soaking steps mitigated the impact of the displacement process on membrane binding capacity and permeability. This suggests that the CPD technique described herein may be used to effectively process and dry delicate porous structures and immobilized ligands. Critical point drying using a modified displacement protocol proved to be a successful method for drying biocompatible membranes, where bioligands are covalently conjugated to the membrane surface. The critical point dried materials had chromatographic performance similar to their pre-dried forms, and their performance and properties remained unchanged when stored in a dry state for extended periods of time.

[0127] Modifications of the typical substitution protocol were necessary for the described CPD process: the incorporation of buffer and salt substitution steps into the protocol allows the medium to withstand the adverse effects resulting from exposure to the fluids and conditions of both the substitution and drying processes.

[0128] The present invention provides the opportunity to use the CPD approach to process and dry a wide range of materials containing sensitive ligands and robust matrices or membranes, or robust bioligands on labile matrices or membranes, or sensitive bioligands immobilized on labile matrices or membranes. In all cases, the CPD process and associated displacement protocols must be modified to accommodate the sensitivity of either the bioligand or the platform on which the ligand is immobilized.

[0129] Incorporation by Reference All U.S. patents and U.S. and international patent application publications cited herein are hereby incorporated by reference.

[0130] Equivalent Those skilled in the art will recognize, or be able to ascertain using no more than routine experimentation, many equivalents to the specific embodiments of the invention described herein which equivalents are intended to be encompassed by the following claims. Other embodiments 1. A method for critical point drying a composite material, comprising: a. providing a composite material comprising: i. a support member comprising a plurality of pores extending therethrough; and ii. a macroporous cross-linked gel comprising a polymer formed from reaction of one or more polymerizable monomers with one or more cross-linking agents; located within the pores of the support member; and wherein the macropores of the macroporous cross-linked gel are smaller than the pores of the support member; b. contacting the composite material with a supercritical fluid at a temperature and pressure above the critical point of the supercritical fluid, wherein gas and liquid phases are indistinguishable; and c. Reducing the pressure Including, This results in critical point drying of the composite material. 2. A method for critical point drying a composite material, comprising: a. providing a composite material comprising: i. a support member comprising a plurality of pores extending therethrough; and ii. a macroporous cross-linked gel comprising a polymer formed from the reaction of one or more polymerizable monomers with one or more cross-linking agents; located within the pores of the support member; and wherein the macropores of the macroporous cross-linked gel are smaller than the pores of the support member, such that the composite material is wetted with an aqueous solution; b. replacing the aqueous solution with a polar organic solvent, wherein the composite material is wetted with the polar organic solvent; c. contacting the composite material with a supercritical fluid at a temperature and pressure above the critical point of the supercritical fluid, where gas and liquid phases are indistinguishable and the polar organic solvent is miscible with the supercritical fluid; and d. Reducing the pressure Including, This results in critical point drying of the composite material. 3. A method for critical point drying a composite material, comprising: a. providing a composite material comprising: i. a support member comprising a plurality of pores extending therethrough; and ii. a macroporous cross-linked gel comprising a polymer formed from the reaction of one or more polymerizable monomers with one or more cross-linking agents; comprising a plurality of ligands which are biomolecules or bioions; and located within the pores of the support member; and wherein the macropores of the macroporous cross-linked gel are smaller than the pores of the support member, such that the composite material is wetted with an aqueous solution; b. replacing the aqueous solution with a polar organic solvent, wherein the composite material is wetted with the polar organic solvent; c. contacting the composite material with a supercritical fluid at a temperature and pressure above the critical point of the supercritical fluid, where gas and liquid phases are indistinguishable and the polar organic solvent is miscible with the supercritical fluid; and d. Reducing the pressure Including, This results in critical point drying of the composite material. 4. The method according to any one of the preceding claims, characterized in that the supercritical fluid is selected from the group consisting of carbon dioxide, water, methane, ethane, propane, ethylene, propylene, methanol, ethanol, acetone, and nitrous oxide. 5. The method according to any one of the preceding embodiments, wherein the supercritical fluid is selected from the group consisting of carbon dioxide, methane, ethane, propane, ethylene, propylene, methanol, ethanol, acetone and nitrous oxide. 6. The method according to any one of embodiments 1 to 3, wherein the supercritical fluid is carbon dioxide. 7. The method according to any one of the preceding claims, characterized in that one or more parameters selected from the group consisting of the total amount of the supercritical fluid relative to the sample volume, the number of purge cycles, the temperature during contact with the supercritical fluid, the replacement rate with the supercritical fluid, the temperature during the evaporation step, the heating rate, and the depressurization rate are adjusted. 8. The method according to any one of embodiments 2 to 7, characterized in that the polar organic solvent is selected from the group consisting of acetone, acetonitrile, ammonia, t-butanol, n-propanol, ethanol, methanol and acetic acid. 9. The method according to any of embodiments 3 to 8, characterized in that the biological molecule or biological ion is selected from the group consisting of albumin, lysozyme, viruses, cells, gamma-globulins of human and animal origin, immunoglobulins of both human and animal origin, proteins of recombinant or natural origin including polypeptides of synthetic or natural origin, interleukin-2 and its receptor, enzymes, monoclonal antibodies, antigens, lectins, bacterial immunoglobulin binding proteins, trypsin and its inhibitors, cytochrome C, myoglobulins, recombinant human interleukins, recombinant fusion proteins, protein A, protein G, protein L, peptide H, nucleic acid derived products, DNA of either synthetic or natural origin, and RNA of either synthetic or natural origin. 10. The method of embodiment 9, wherein the biological molecule or biological ion is protein A. 11. The method of any one of the preceding claims, wherein the support member comprises a polymeric material selected from the group consisting of polysulfone, polyethersulfone, polyphenylene oxide, polycarbonate, polyester, cellulose, and cellulose derivatives. 12. The method according to any one of the preceding claims 1 to 11, wherein the composite material is a membrane. 13. The method according to any one of the preceding claims, wherein the composite material is in contact with one or more interleaf layers. 14. The method of embodiment 13, wherein the one or more interleaf layers are selected from the group consisting of screen, polypropylene, polyethylene, and paper. 15. The method according to any one of the preceding embodiments, wherein the crosslinked gel is a neutral hydrogel, a charged hydrogel, a polyelectrolyte gel, a hydrophobic gel, a neutral gel, or a gel containing functional groups. 16. The method of any one of embodiments 1 to 15, wherein the macroporous crosslinked gel comprises macropores having an average size of about 10 nm to about 3000 nm. 17. The method of any one of embodiments 1 to 16, wherein the pores of the support member have an average pore diameter of about 0.1 μm to about 50 μm.

Claims

1. A method for critical point drying of a composite material for the separation and purification of biomolecules, comprising: a. providing a composite material comprising: i. a support member comprising a plurality of pores extending therethrough; and ii. a macroporous cross-linked gel comprising a polymer formed from the reaction of one or more polymerizable monomers with one or more cross-linking agents; located within the pores of the support member; and wherein the macropores of the macroporous cross-linked gel are smaller than the pores of the support member, such that the composite material is wetted with an aqueous solution; b. replacing the aqueous solution with a polar organic solvent, wherein the composite material is wetted with the polar organic solvent; c. contacting the composite material with a supercritical fluid at a temperature and pressure above the critical point of the supercritical fluid, where gas and liquid phases are indistinguishable and the polar organic solvent is miscible with the supercritical fluid; and d. Reducing the pressure Including, This results in critical point drying of the composite material, characterized in that the composite material is a membrane and the macroporous cross-linked gel comprises a plurality of ligands that are biomolecules or bioions.

2. 2. The method of claim 1, wherein the supercritical fluid is selected from the group consisting of carbon dioxide, water, methane, ethane, propane, ethylene, propylene, methanol, ethanol, acetone, and nitrous oxide.

3. 2. The method of claim 1, wherein the supercritical fluid is selected from the group consisting of carbon dioxide, methane, ethane, propane, ethylene, propylene, methanol, ethanol, acetone and nitrous oxide.

4. 2. The method of claim 1, wherein the supercritical fluid is carbon dioxide.

5. 5. The method according to claim 1, characterized in that one or more parameters selected from the group consisting of the total amount of the supercritical fluid relative to the sample volume, the number of purge cycles, the temperature during contact with the supercritical fluid, the replacement rate with the supercritical fluid, the temperature during the evaporation step, the heating rate and the decompression rate are adjusted.

6. 6. The process according to claim 1, wherein the polar organic solvent is selected from the group consisting of acetone, acetonitrile, ammonia, t-butanol, n-propanol, ethanol, methanol and acetic acid.

7. 7. The method according to any one of claims 1 to 6, characterized in that the biomolecule or bioion is selected from the group consisting of albumin, lysozyme, viruses, cells, gamma globulins of human and animal origin, immunoglobulins of both human and animal origin, proteins of recombinant or natural origin including polypeptides of synthetic or natural origin, interleukin-2 and its receptor, enzymes, monoclonal antibodies, antigens, lectins, bacterial immunoglobulin binding proteins, trypsin and its inhibitors, cytochrome C, myoglobulins, recombinant human interleukins, recombinant fusion proteins, protein A, protein G, protein L, peptide H, nucleic acid derived products, DNA of either synthetic or natural origin, and RNA of either synthetic or natural origin.

8. The method according to claim 7, characterized in that the biomolecule or bioion is protein A.

9. 9. The method of claim 1, wherein the support member comprises a polymeric material selected from the group consisting of polysulfone, polyethersulfone, polyphenylene oxide, polycarbonate, polyester, cellulose, and cellulose derivatives.

10. A method according to any one of claims 1 to 9, characterized in that the composite material is in contact with one or more interleaf layers.

11. 11. The method of claim 10, wherein the one or more interleaf layers are selected from the group consisting of screen, polypropylene, polyethylene, and paper.

12. The method according to any one of claims 1 to 11, characterized in that the crosslinked gel is a neutral hydrogel, a charged hydrogel, a polyelectrolyte gel, a hydrophobic gel, a neutral gel, or a gel containing functional groups.

13. The method according to any one of claims 1 to 12, characterized in that the macroporous crosslinked gel comprises macropores with an average size between 10 nm and 3000 nm.

14. A method according to any one of the preceding claims, characterized in that the pores of the support member have an average pore diameter of from 0.1 μm to 50 μm.

Citation Information

Patent Citations

  • Chromatographic films formed by thiol-ene or thiol-click polymerization reactions

    JP2018511667A

  • Laminates containing reinforced aerogel composites

    JP2019503292A

  • Process for the production of highly organized crystals by means of Sol-Gel methods

    US20050238561A1

  • Sol composition, aerogel composite, support member provided with aerogel composite, and heat insulator

    WO2017164184A1